The Role of Location in Everyday Experiences of Music - Krause, Amanda; North, Adrian; Hewitt, Lauren (American Psychological Association, 2014)
Mehrabian and Russell’s (1974) Pleasure–Arousal–Dominance model states that a propensity to approach/avoid an environment can be conceptualized in terms of the pleasure and arousal it elicits and one’s degree of dominance therein. Using the Experience Sampling Method, 177 individuals provided responses concerning Mehrabian and Russell’s model throughout 1 wk regarding music experiences that occurred in their daily life (including how the music was heard and how their responses related to the listening location). Results indicate that the time of day and day of week are related to where music is experienced, and that the consequences of what was heard are related to both time and location. Although music was experienced more often in private locations than in public overall, interesting patterns of music experiences that occurred in public locations demonstrate in detail how music listening varies by location. Specifically, portable devices were associated with positive responses, which contrasted sharply with the responses to music broadcasted publicly in public settings. Participants’ ratings of choice, liking, and arousal demonstrated the importance of considering choice as an indication of dominance, such that music usage is consistent with Mehrabian and Russell’s model, and has functions that vary according to the specific characteristics of the situation.